AB0428 Demographics, organ involvement and medications in sle patients from six countries in asia-pacific. (23rd January 2014) - Jakes, R.; Navarra, W. S.; Jain, P.; Louthrenoo, W.; Bae, S.-C.; Hoi, A.; Kong, N. C. T.; Koolvisoot, A.; Lin, H.-Y.; Nash, P.; Weng, M.-Y.
Abstract : Background: Systemic lupus erythematosus (SLE) may vary in presentation and management approach in different geographies (1 ). A review of the literature describing the epidemiology of SLE in Asia-Pacific countries identified a dearth of information on the characteristics and perceived wide variability in management of lupus in the region (2 ). This study was designed to observe SLE patients and their care, from six countries in Asia-Pacific, under a common protocol, over a twelve month follow-up period. This abstract describes the baseline features of the cohort. Objectives: The aim of the study is to describe patient characteristics, organ involvement, disease activity and severity, and management in a multi-national observational cohort. Methods: Patients were invited to participate from lupus clinics in six countries (nine centres), between April and October 2012. Consecutive patients, 18 years or older, meeting at least four ACR criteria for diagnosis of SLE were eligible. Information describing organ system involvement, disease activity and severity, and management of the patients were recorded. Severe disease was defined as a) at least one of the major domains: cardiovascular, respiratory, renal or urological actively involved (biologically active eg proteinuria or symptomatic) at enrolment, and b) requiring more than 7.5mg/d of corticosteroids (prednisone equivalent dose) and/or immunosuppressant(s) and/or biological drugs. Results: 553 patients (404, 92% women) were recruited. Mean age at SLE diagnosis was 28.8 (SD 11.4) years, and mean number of years since diagnosis was 9.2 (SD 6.7). For disease activity profile at entry into the study, the most common domain of active disease involvement was renal disease (17% of patients). Similarly, the domain most reported as being damaged (non-reversible change not related to active inflammation) since onset of lupus was renal (9%). 20% of the patients were classified as having severe disease, with Taiwan showing the highest proportion of severe disease (39%), and South Korea the lowest proportion (14%). Steroid use was reported in 81.6%, anti-malarials in 63.2%, immunosuppressants in 48.3% and a biological drug in one patient (0.2%). Conclusions: We have provided a cross-sectional overview of the demographics, disease characteristics and therapies in a cohort of SLE patients seen at selected sites across 6 countries in Asia-Pacific. A high proportion of patients, at the time of enrolment, were managed with steroids, anti-malarials and immunosuppressants, with one patient receiving biological therapy. This sets the baseline for a one-year observational study utilizing a standard electronic case report form, in order to better understand the behavior and management practice of SLE in the region. References: Danchenko et al. Epidemiology of systemic lupus erythematosus. Lupus 2006; 15: 308-18. Jakes RW et al. Systematic review of the epidemiology of systemic lupus erythematosus in Asia-Pacific. ACR 2012; 64: 159-168. Disclosure of Interest: R. W. Jakes Shareholder of: GSK, Employee of: GSK, S. Navarra Grant/research support from: GSK, Speakers bureau: GSK, Roche, P. Jain Shareholder of: GSK, Employee of: GSK, W. Louthrenoo: None Declared, S.-C. Bae: None Declared, A. Hoi Grant/research support from: UCB, Eli Lilly, Suppremol, GSK, Consultant for: BMS, Speakers bureau: Abbott, BMS, MSD, Mundipharma, UCB, N. C. T. Kong Grant/research support from: GSK, A. Koolvisoot: None Declared, H.-Y. Lin: None Declared, P. Nash Grant/research support from: GSK, Consultant for: GSK, M.-Y. Weng: None Declared